Current Status of State Management of Publishing Activities - A Case Study in Ho Chi Minh City – Vietnam - Thanh, Nguyen Van; Le, Dang Thanh; Tuan, Luc Anh; Hung, Cao Thanh; Do, Do Thanh (Journal of Posthumanism, 2024)
State management of publishing activities is becoming increasingly vital for countries, as it helps promote national culture, guides the cultural values of ethnic communities, and shapes the ideologies of political parties and systems. This study aims to assess the current state management of publishing activities in Ho Chi Minh City, which serves as Vietnam’s leading center for economics, finance, culture, society, education, training, science, and technology. Data for this study was gathered through an analysis and summary of secondary documents, along with sociological surveys conducted using questionnaires distributed to 120 state management personnel involved in publishing activities, as well as 186 leaders and employees from publishing houses, enterprises, and individuals engaged in printing, publishing, and distribution in Ho Chi Minh City. The research findings indicate that, despite some successes, there are still certain limitations in the management of publishing activities in Ho Chi Minh City. These results will serve as a foundation for developing appropriate solutions to enhance the efficiency of management in the city.